(untitled) - Hoque, M.Z. (Rome, 1989)
Contents: Rice is gaining increasing prominence in the diets and farming systems of Africa. In several countries, it has already assumed the status of a stape food.
Keywords: Lúa,Rice; Trồng,Breeding